Genetic characterisation of the ethambutol resistance-determining region in Mycobacterium tuberculosis - Perdigao, Joao (2015)
Ethambutol (EMB) is a first-line antitubercular drug that inhibits arabinogalactan and lipoarabinomannan biosynthesis. Resistance to EMB has traditionally been associated with embB mutations, especially in the Met306 codon. In this study, the region encom. - Fundacao Calouste Gulbenkian, Lisbon, Portugal [FCG 001013]. - Funding: This work was supported by Fundacao Calouste Gulbenkian, Lisbon, Portugal (grant FCG 001013).